Design and Analysis of High-Speed FSO for Supporting Fifth Generation under various weather scenarios - Mays Kifah Faeq; Alaan Ghazi; Mohammed U.Zaenal; Lana Omar; Ranjdr M. Rafeeq; Ibrahim Jasim; Mohammad Sarwar; Ahmed Ghazi (Zien Journals, 2022)
5G is expected to change the mobile communications environment by boosting data throughput, improving energy efficiency, expanding coverage, and lowering latency. FSO is a high-capacity, efficient, and scalable 5G architecture for transmitting radio signals via optical communication, taking use of the massive bandwidth available. In this research design MDM over FSO in various weather scenarios. This paper investigated the performance of BER and Q-Factor over different distances of over FSO in various weather scenarios based MDM. This study has transmitted 30 Gbit/s based on three channels. Furthermore, the results demonstrated that 3x 10 Gbit/s MDM-FSO system (various weather scenarios) in an optical wireless communication system, it is useful at improving data quality
Keywords: MDM; FSO; different weather conditions